Filosofi Dan Etika Hindu Dalam Pantangan Membaca Dan Menulis Pada Hari Suci Saraswati - Putu Sabda Jayendra (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2020)
The existence of a myth that has developed among Hindus in Bali regarding the prohibition of reading and writing on the holy day of Saraswati is still perceived by the Hindu community as something contradictory. Saraswati Day, as a holy day for the decline of knowledge, has restrictions on not reading and writing. This raises pros and cons among the Balinese Hindu community. Conservative community groups consider that this is a provision that cannot be questioned and criticized. But on the other hand, millennials who tend to be progressive are trying to criticize this. In fact, the prohibition of reading and writing on the holy day of Saraswati has a philosophy and ethical values which, when understood, will arrive at a meeting point between myth and rationality. Through this paper, we will discuss the philosophical meaning and ethical values of the prohibition of reading and writing on the holy day of Saraswati based on Hindu teachings